Analisa Hubungan antara Size, Product Life Cycle, dan Market Position dengan Penggunaan Balanced Scorecard pada Sektor Perbankan dan Asuransi di Surabaya - Aprillycia Tanoyo (Business Accounting Review, 2013)
Increasingly stringent of banking and insurance competition makes every bank and insurance must be active to improve their performance. Measuring organizational performance in advance can be used to guide the managers to formulate the necessary improvements. A performance measurement tool that can be used is the balanced scorecard which is not only measure performance of the financial side, but also the non-financial. The study aimed to examine the relationship among size, product life cycle, and market position and the use of a balanced scorecard in the banking and insurance sectors in Surabaya. In this study, balanced scorecard is referes to the use of the balanced scorecard framework as a performance measurement. This study used a sample taken from the June 2012 issue of Investor Magazine that were the 50 best banks in 2012 and from the July 2012 issue of Investor Magazine were the 20 best insurance companies in 2012 with the headquarters or branches in Surabaya. The hypothesis was tested by using Pearson Product Moment Correlation. The study shown that there was a relationship among organization size, product life cycle, and market position, and the use of the balanced scorecard. Also, the study shown that the use of the most balanced scorecard is at the customer's perspective, which amount to 25,78%